(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The article analyzes Law No. 180/1978, highlighting its role in balancing individual self-determination and public function. It examines judicial and constitutional aspects, with a particular focus on compulsory medical treatments and the limits on the exercise of political rights. The study reveals how public functions have evolved as safeguards for collective interests, moving beyond traditional approaches. Critical reflections emerge on the boundaries between individual freedom and social responsibility. The Basaglia Law is reaffirmed as a turning point in the affirmation of human dignity in law.